Commercial Dynamism of the Andean Community: An Analysis of the Diversification of Its Products and Markets - Constantino Muñoz, Angélica María; Rosillo Carrillo, Susan Selene; Montalvan Gonzales, Atenas; Montes Ninaquispe, Jose Carlos; Zegarra Escudero, Homero Teofilo (LACCEI, 2024)
The general objective was to describe the commercial dynamism of the Andean Community during the period 2019-2023. A quantitative approach was adopted, utilizing data from Trade Map to analyze product and market diversification, employing the Herfindahl-Hirschman Index (HHI) as a diversification indicator. Bolivia experienced significant growth in the export of animal fats and oils (140.63%) and prepared animal feeds, although its mineral fuel exports fell by 24.58%. China was the main growth destination for Bolivia (190.35%), and its HHI showed a continuous decline, reflecting greater market diversification. Colombia notably diversified its exports with significant growth in manufactured products and technological services, and India was its fastest-growing market (592.20%), although the HHI showed fluctuations. Ecuador showed an increase in diversification with agro-industrial products such as shrimp and flowers, and Panama was its fastest-growing market (133.12%), with a decreased HHI reflecting successful diversification. Peru diversified its exports with an increase in sectors such as mining and agro-industry, highlighting copper minerals and fresh grapes, although it showed increasing concentration in markets such as China and the United States, reflected in its HHI. The Andean Community has made progress in product and market diversification, reducing its economic vulnerability.